1997
DOI: 10.1200/jco.1997.15.4.1560
|View full text |Cite
|
Sign up to set email alerts
|

Serum aminotransferase elevation during and following treatment of childhood acute lymphoblastic leukemia.

Abstract: Our data show that MTX can be safely delivered without dose modification in patients with isolated ALT elevations and that continued therapy does not lead to clinically apparent liver disease. ALT elevations are not a reliable predictor of the presence or extent of hepatic injury, and persistently increased ALT values following the completion of ALL therapy are rare in the absence of HCV infection. Continued MTX therapy allows for increased dose-intensity and may improve outcome in children with ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 38 publications
3
21
1
Order By: Relevance
“…Elevated ALT was common during therapy and this finding is in accordance with the recent study by Farrow et al [40], who reported that 66.5% of children with ALL had an ALT level of 180 U/L or more during therapy, and that 17.6% had at least one ALT value of 720 U/L or more. Several small earlier studies have documented that the extent of aminotransferase elevation is not predictive of abnormal liver histology [10,12,35,36].…”
Section: Discussionsupporting
confidence: 93%
“…Elevated ALT was common during therapy and this finding is in accordance with the recent study by Farrow et al [40], who reported that 66.5% of children with ALL had an ALT level of 180 U/L or more during therapy, and that 17.6% had at least one ALT value of 720 U/L or more. Several small earlier studies have documented that the extent of aminotransferase elevation is not predictive of abnormal liver histology [10,12,35,36].…”
Section: Discussionsupporting
confidence: 93%
“…Methotrexate is sporadically associated with fatty liver disease, fibrosis, and cirrhosis during long-term treatment at immunosuppressive doses [19, 20]. Hepatocellular injury and acute liver failure have also been described during its use as an antineoplastic agent, but not in combination with microvesicular steatosis [21,22,23]. Neither daunorubicin or vincristine nor prednisone are related to acute liver injury or the development of microvesicular hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, most study groups do not recommend dose reductions in case of high aminotransferase levels48 unless accompanied by biochemical evidence of severe hepatic dysfunction, that is, bilirubin 3 times above the upper normal limit and/or coagulation factor II-VII-X <0.50 IU/L. Such patients should be explored for other causes, including hepatotropic vira (eg, B or C virus153,154), veno-occlusive syndrome (VOD), or Gilbert syndrome with reduced glucuronyltransferase activity and elevated unconjugated bilirubin.…”
Section: Toxicity and Relapse Ratementioning
confidence: 99%